High magnetization reversal barriers in luminescent dysprosium octahedral and pentagonal bipyramidal single-molecule magnets based on fluorinated alkoxide ligands. Issue 24 (28th May 2021) - Long, Jérôme; Tolpygin, Aleksei O.; Lyubov, Dmitry M.; Rad'kova, Natalia Yu.; Cherkasov, Anton V.; Nelyubina, Yulia V.; Guari, Yannick; Larionova, Joulia; Trifonov, Alexander A.
Abstract : Three luminescent single-molecules magnets based on different fluorinated alkoxide ligands and exhibiting high magnetization reversal barriers are reported. Abstract : We report the synthesis and structures of three luminescent dysprosium(iii ) complexes based on fluorinated alkoxide ligands of formulas [Dy(L 1 )2 (THF)4 ][BPh4 ]·0.5THF (1 ), [Dy(L 2 )2 (THF)5 ][BPh4 ]·2.5THF (2 ) and [Dy(L 3 )2 (THF)5 ][BPh4 ]·2THF (3 ) (L 1 = (CF3 )3 CO −, L 2 = C6 F5 C6 F4 O −, L 3 = C6 F5 C(CH3 )O − ). Despite the different dysprosium ion geometries (octahedral vs. distorted pentagonal bipyramidal), these systems exhibit a single-molecule magnet (SMM) behavior, but with distinct relaxation dynamics. Moreover, a typical dysprosium-based luminescence is observed for the three complexes, which make them bifunctional magneto-luminescent SMMs. Remarkably, complex 3 exhibits a high anisotropy barrier of 1469 cm −1 and a blocking temperature of 22 K, making it one of the most performant alkoxide-based SMMs with the highest blocking temperature for a luminescent SMM.